Social Policy in South Africa: the challenges of Poverty, Inequality and Exclusion - Ina Conradie (Social Work & Society, 2019)
South Africa is currently emerging from a political and socio-economic crisis. A political faction largely based on patrimonialism threatened to destroy the economy and thus social service delivery. With the recent election of Cyril Ramaphosa as State President a new start has been made to build a successful economy which can act as a base for pro-poor policies. This process will however not be easy. Although South Africa is known as the welfare leader in Africa, with 45.5% of its population receiving welfare grants, these social grants are not large enough to alleviate poverty, and almost 54% of the population remains under the poverty line. The National Planning Commission of South Africa is attempting to institute a comprehensive social security floor to cover all possible needs of the poor and excluded, but with the numbers cited above this remains a difficult undertaking. I will argue that a range of interventions is necessary to address this complex situation. The comprehensive social security floor at a low- income level is important. This will contribute to the alleviation of high levels of extreme poverty found at present. However, South Africans are highly aspirational and most of the poor aspire to "a better life." The National Development Plan therefore also proposes welfare programmes which can act as a leverage into economic activity. An example of such a programme would be the proposed social security programme for informal workers (Devereux and Conradie, 2015).